Ghana’s macroeconomic crisis: Causes, consequences, and policy responses - Younger, Stephen D. (International Food Policy Research Institute, 2016)
Ghana is in the midst of a severe but not unprecedented macroeconomic crisis. This paper helps to evaluate the government’s policy options by (1) explaining the crisis’ causes, and (2) comparing it to previous macroeconomic crises and the policies that corrected them. Two large shocks are to blame for the crisis: an increase in the fiscal deficit of about 6 percent of GDP and a reduction in hydroelectric production that has not been replaced with thermal generation. This latter is more difficult to quantify, but may be as large as 4 percent of GDP. While large, Ghana has recovered from similar shocks in the past, and with luck, should be able to do so now. But this will require reversal of the large increases in the public sector wage bill that drove much of the fiscal shock.